2012
DOI: 10.1016/j.ccr.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures Uncover Distinct Targets in Molecular Subsets of Diffuse Large B Cell Lymphoma

Abstract: SUMMARY Molecular signatures have identified several subsets of Diffuse Large B-Cell Lymphoma (DLBCL) and rational targets within the B-cell receptor (BCR) signaling axis. The OxPhos-DLBCL subset, which harbors the signature of genes involved in mitochondrial metabolism, is insensitive to inhibition of BCR survival signaling, but is functionally undefined. We show that compared with BCR-DLBCLs, OxPhos-DLBCLs display enhanced mitochondrial energy transduction, greater incorporation of nutrient-derived carbons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

30
485
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(516 citation statements)
references
References 43 publications
30
485
0
1
Order By: Relevance
“…The OCI-Ly7 cell line, the in vitro model bearing the 11q24.3 gain, is usually considered of GCB origin but is more likely representative of a type of DLBCL intermediate between GCB and ABC DLBCL. 35 Indeed, also in our hands, the cell line expressed markers typical of both GCB (BCL6, PAX5) and non-GCB DLBCL (IRF4, PRDM1, XBP1) (data not shown). These observations suggest that the lesion might be relevant in a subgroup of DLBCL derived from the non-GC phase in accordance with the observed higher ETS1 RNA levels in ABC than in GCB DLBCL.…”
Section: Discussionmentioning
confidence: 94%
“…The OCI-Ly7 cell line, the in vitro model bearing the 11q24.3 gain, is usually considered of GCB origin but is more likely representative of a type of DLBCL intermediate between GCB and ABC DLBCL. 35 Indeed, also in our hands, the cell line expressed markers typical of both GCB (BCL6, PAX5) and non-GCB DLBCL (IRF4, PRDM1, XBP1) (data not shown). These observations suggest that the lesion might be relevant in a subgroup of DLBCL derived from the non-GC phase in accordance with the observed higher ETS1 RNA levels in ABC than in GCB DLBCL.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have shown that utilization of alternative carbon sources affects tumor evolution, and the role of oxidative phosphorylation in cancer metabolism has not been fully appreciated (46,(51)(52)(53)(54). Furthermore, the ability of normal as well as cancer cells to rapidly adjust their metabolic behavior in response to environmental conditions and cellular requirements is essential to survival and the metabolic requirements of proliferating and nonproliferating cells are distinct, as are the metabolic demands underlying tumor initiation, metastasis, and growth at distant sites (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CCC-defined BCR-DLBCLs include BCR-dependent tumors of both ABC and GCB COO subtypes, 16,17 whereas CC-classified OxPhos-DLBCLs include BCRindependent tumors. 7,16 Our previous functional analyses of DLBCL subtypes also uncovered quantitative proteome-and metabolome-level signatures associated with differences in nutrient and energy metabolism. 7 Specifically, these studies showed that BCR-dependent DLBCLs have greater glycolytic flux typical of the Warburg phenotype.…”
mentioning
confidence: 99%
“…For example, CCC-defined BCR-DLBCLs include BCR-dependent tumors of both ABC and GCB COO subtypes, 16,17 whereas CC-classified OxPhos-DLBCLs include BCRindependent tumors. 7,16 Our previous functional analyses of DLBCL subtypes also uncovered quantitative proteome-and …”
mentioning
confidence: 99%
See 1 more Smart Citation